Conceptualising and measuring householder bushfire (wildfire) risk perception: The householder bushfire risk perception scale (HBRPS-4). (January 2022) - Hall, Andrew; McLennan, Jim; Marques, Mathew D.; Bearman, Christopher
Abstract: With increasing numbers of householders living in high bushfire (wildfire) risk areas, there is a need to better understand householders' bushfire risk perceptions. In the community bushfire safety research literature, there appears to be no consensus on how best to conceptualise and measure householders' bushfire risk perceptions. The aim of this research was to investigate the concept of bushfire risk perception and its measurement, and to develop a brief, reliable and valid measure of householders' bushfire risk perceptions. Following a review of 26 studies, a four-item householder bushfire risk perception scale (HBRPS-4) was developed. Analysis of responses to an online survey of 375 householders indicated that the measure had high internal consistency (α = 0.93). There was evidence of: construct validity, concurrent convergent criterion validity (| r | range 0.21–0.58), and concurrent discriminant criterion validity ( r  ≤ 0.15). A supplementary study with 27 participants found a high level of test-retest reliability over a six-week period ( r  = 0.95). It is suggested that householder bushfire risk perception can be construed as a fuzzy concept, incorporating three risk perception elements (probability, consequences, concern) whose meaning boundaries are not well-differentiated. The HBRPS-4 appears to hold promise of being a useful measure for community bushfire safety research.